How Self-compassion Affects Work Engagement: Examining the Moderating Role of Difficulties in Emotion Regulation and Interpersonal Stress - Liu, Sen; Chen, Ching Chou (Journal of China-ASEAN Studies, 2022)
This article aims to explore whether the level of employees’ self-compassion has an impact on their own performance in the organization. And, this article explores related variables to establish a theoretical model, use the questionnaire survey method, through the network questionnaire, and collect 335 valid samples for analysis. The results show that selfcompassion has a negative impact on emotional exhaustion, emotional exhaustion has a negative impact on work engagement, difficulties in emotional regulation have a negative moderating effect between self-compassion and emotional exhaustion. Moreover, selfcompassion can alleviate the negative impact of employees when they are under pressure, bring benefits to the employees themselves, and lead to the employees having a positive impact on the organization.